Stylistic Analysis of Ahmed Ali’s Short Story Our Lane - Muhammad Tufail Chandio; Faraz Ali Bughio; Abdul Hameed Panhwar; Sikander Munir Memon (Journal of Education and Educational Development, 2020)
The undertaken study is based on stylistic analysis of Ahmed Ali’s short story Our Lane. The study analyzes how the author has used linguistic features like noun, adjective, conjunction, sentence complexity to portray the social, political, economic, religious, psychological and cultural conditions of the colonized natives of the Indian subcontinent in the wake of the British colonial rule. The story portrays how the colonial rule has deteriorated the people socially, economically, politically and psychologically. Ahmed Ali’s use of adjective is in consonant with the established norm of using 7 to 8% of the total text (Hofland & Johansson, 1987:6). Whereas, the median of 343 sentences is 13, which is shorter than the length of an average modern sentence, which according to Ellegard is 17.8 words. While rebutting colonial narrative, he deviates from the standards of English language: excessive use of coordinating conjunction ‘and’ is evidence to it. Most adjectives of positive characteristics qualify to the past, whereas the adjectives referring to present are either of negative or of neutral characteristics, and thus the writer recognizes the glory of the past and condemns the disintegrating present and uncertain future in the colonized land.
Keywords: colonialism; Indian subcontinent; Our Lane; post colonialism; stylistics